Electronic reference services: a quality and satisfaction evaluation. Issue 2 (10th June 2019) - Gómez-Cruz, M. Elena
Abstract : Purpose: An evaluation of libraries and their overall quality should consider the quality of the services they provide. Satisfaction in terms of the service provided is indicative of the quality of reference services and since these services are expensive, evaluation is therefore essential. This paper aims to outline the development of a structural equations model to evaluate service quality and user satisfaction with regard to the electronic reference service provided by Francisco Xavier Clavigero Library belongs to the Iberoamericana University, located in Mexico City. Design/methodology/approach: This model suggests that service quality can be explained by way of the five dimensions of the SERVQUAL methodology, (reliability, assurance, tangibles, empathy and responsiveness) and in turn, quality explains both user satisfaction and the value of the service to its patrons. Finally, this model suggests that a positive increase in user satisfaction leads to a lineal and positive increase in user loyalty. The evaluation considered 297 users who made at least one electronic reference request during 2014. Findings: The adjustment of the structural model reveals that the latent variables that explain quality are reliability and responsiveness, and that quality explains satisfaction, which in turn explains user loyalty. Originality: The generation of an indicator to evaluate the reference services enables identification of its strengths and weaknesses to offer a more efficient service, considering that it represents a significant percentage of the library's financial and human resources.